Analisis Pemahaman Konsep Siswa Pada Pembelajaran Matematika Di Kelas IV SD Negeri Kampung Bayur Kabupaten Tangerang - Hikmatulfazriyah, Sri; Sunardin, Sunardin; Unaenah, Een (Jurnal Ilmiah Wahana Pendidikan, 2023)
Sri Hikmatulfazriyah "Analysis of students' understanding of concepts in learning mathematics in class IV SD Negeri Kampung Bayur, Tangerang Regency". This study aims to describe students' understanding of concepts in learning mathematics in class IV SDN Kampung Bayur, Tangerang Regency. Mathematics is a science that is taught at every level of education, it is hoped that it can contribute to developing the ability to think critically, systematically, logically, creatively, and work together effectively. The method used in this study is descriptive qualitative using data collection techniques in the form of tests, interviews and documentation. Checking the validity of the data using triangulation. Data were analyzed through the steps of data collection, data reduction, and drawing conclusions. Respondents in this study totaled 10 people, namely class IV A students. The conclusions from observations and interviews in the study showed that students could understand mathematics learning according to the seven indicators of understanding concepts.